PENERAPAN SYSTEM DEVELOPMENT LIFE CYCLE (SDLC) DALAM MENGEMBANGKAN FRAMEWORK AUDIO FORENSIK - Rahmat Inggi; Bambang Sugiantoro; Yudi Prayudi (semanTIK, 2018)
An audio recorder is one of the multimedia content that is often found at the crime scene and is used as evidence in the trial process. Audio recorders that can be made as legal evidence in court must follow the rules and audio forensic standards that apply in the process of obtaining the evidence, this is because audio digital evidence is very easy to manipulate. The forensic audio investigation process requires a framework that can be used as a reference in the investigation process. However, at present, the developing audio forensic focus more on analyzing audio forensic techniques and does not provide more specific stages in handling forensic audio from the scene of the case to the trial process. This research focuses on developing the audio forensic framework by implementing the Systems Development Life Cycle (SDLC) in the process of developing the forensic audio framework. Systems Development Life Cycle (SDLC) has stages of planning, analysis, design, implementation, and maintenance that are often used as references in the process of making and developing systems. In other words, the implementation of this method will enable researchers to develop an audio forensic framework that can be used as a standard in conducting the forensic audio investigation process.Keywords—Audio Recorder, Audio Forensics, Framework, SDLCDOI : 10.5281/zenodo.2528444